Economic Recovery in Response to Worldwide Crises: Fiduciary Responsibility and the Legislative Consultative Process with Respect to Bill 150 (Green Energy and Green Economy Act, 2009) and Bill 197 (COVID-19 Economic Recovery Act, 2020) in Ontario, Canada - Tsuji, Stephen R. J. (The International Indigenous Policy Journal, 2022)
The Green Energy and Green Economy Act was quickly passed in 2009. Due to the breadth of the Act, it should have received a rigorous legislative review-and-consultation process, but did not due to green-labeling. Ontario did not meet their ethical fiduciary responsibility to consult with Indigenous peoples. With the COVID-19 Economic Recovery Act, 2020, there were no public hearings even though changes to the Environmental Assessment Act would allow for the exemption or streamlining of projects from the process. If a project was exempted, there would be no environmental assessment, and no legal fiduciary responsibility to consult with Indigenous peoples; the legal duty to consult would not be triggered even though Indigenous peoples would potentially be impacted. Rather than noting an improvement in the legislative consultative process since 2009, there has been a regression.